Produktivitas Pertambangan Batubara Terhadap Pertumbuhan Ekonomi di Provinsi Kalimantan Selatan - Sapitri, Nordina; Sopiana, Yunita (PPJP ULM, 2025)
This study aims to analyze the influence of coal price productivity, coal production and mining land area on economic growth in South Kalimantan Province in 1990-2020. The type of research used is quantitative research, using multiple linear regression analysis. The data was obtained from the South Kalimantan Province Central Statistics Agency and the South Kalimantan Province Energy and Mineral Resources Service. The research results show that coal prices, coal production and mining land area simultaneously have a significant effect on economic growth in South Kalimantan Province. Then, partially coal prices and mining land area have a positive and significant effect and coal production has a negative and significant effect on the economic growth of South Kalimantan Province in 1990-2020.